Can contract marketing motivate farmers to go organic? Measuring the moderation effect of contract marketing - Rezai, Golnaz; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Ting, Jenn Ling (Science Publications, 2016)
The demand for organic food is growing in Malaysia due to consumer concerns for food safety, sustainable development and urban expansion. However, the share of farmers engaged in this type of agriculture in Malaysia is notably low with only 72 (0.02%) organic vegetable farmers out of a total of 272, 000 farmers in the country. Therefore, it is crucial to understand why the majority of the farmers do not practice organic farming and suggest possible solutions through contract marketing as a motivating tool to enhance their participation in organic farming. In this study, a total of 329 conventional vegetable farmers were selected and interviewed through multi-stage systematic random sampling method via a structured questionnaire. Factor analysis and hierarchical multiple regression analysis has revealed that there is a moderating role by contract marketing to strengthen the relationship between attitude and public farmers’ intention to practice organic farming. This study has identified contract marketing as a component which moderates the perceived behavioral control-intention to practice organic farming. Therefore, contract farming not only shapes the attitude of farmers but it also develops the control over the chain by channeling farmers’ products to the buyers.